Pendidikan Agama Islam di Sekolah Umum (Persfektif Histori) - Juniarti Iryani; Bahaking Rama; Muhammad Yahdi (CV Putra Publisher, 2023)
The purpose of this study is to describe and analyze Islamic religious education in public schools in terms of history. The research method used is a qualitative research method with library research (Library research). Source data (primary) in the form of journals and other reading sources relating to the history of Islamic Religious Education in public schools. Data management is entirely